Karakteristik Pengembangan Media Pembelajaran untuk Menguatkan Ekoliterasi Siswa SMA di Era Revolusi Industri 4.0 - Nurul Faiqoh; Puguh Karyanto; Meti Indrowati (Proceeding Biology Education Conference: Biology, Science, Enviromental, and Learning, 2019)
Learning media are developed based on the needs in learning to support the pursuit. Media needs in the banking industry because of material problems, inadequate school infrastructure. The study aimed to study the characteristics of the development of instructional media to strengthen the eco-literacy students at Al Islam 1 High School Surakarta. Development of learning media is included in R & D research (research and development) that can be done with the 4D model which consists of defining, designing, developing, and analyzing. Determination of the characteristics of the media is carried out on a set of definitions consisting of the initial analysis, task analysis, student analysis, and analysis. Analysis of instruments used in the form of draft interviews, questionnaires, questions, and NEP instruments. The subjects of the study were taken by purposive random sampling technique on the XI grade students totaling 50 students. The results of the study indicate the fact that learning media that need to be developed are made in the form of digital learning to support school facilities and are equipped with material specifically for ecosystems. Learning media as much as possible facilitates student practical activities so that they continue to carry out practicum outside the school, but still under the supervision of the teacher in the form of a database.